Characteristics of different charge transfer modes in upward flashes inferred from simultaneously measured currents and fields. Issue 1 (1st February 2020) - He, Lixia; Azadifar, Mohammad; Li, Quanxin; Rubinstein, Marcos; Rakov, Vladimir A.; Mediano, Arturo; Pavanello, Davide; Rachidi, Farhad
Abstract : The authors present an analysis of different charge transfer modes during upward negative flashes. The analysis includes a total number of 94 pulses that occurred during two upward negative flashes recorded at the Säntis Tower. The pulses included 59 mixed‐mode (MM) initial continuous current (ICC) pulses, 17 M‐component‐type ICC (M‐ICC) pulses, 8 return‐stroke pulses, and 10 classical M‐component (MC) pulses. It is found that the initial stage of the flash is responsible for the largest share of the total charge transferred to the ground. Simulation results for the electric fields associated with the considered charge transfer modes are presented and discussed. Return stroke (RS) and MM pulses were simulated adopting the MTLE model, while MCs and M‐ICC pulses were simulated using the guided wave model of Rakov et al. The simulated results are shown to be in good agreement with simultaneous records of electric fields measured at a distance of 15 km from the Säntis Tower. The inferred velocities for MCs and M‐ICC pulses range from 2.0 × 10 7 to 9.0 × 10 7 m/s, and the corresponding junction point heights range from 1.0 to 2.0 km. The inferred pulse velocities for RSs and MM pulses range from 1.3 × 10 8 to 1.65 × 10 8 m/s. The inferred current attenuation constants of the MTLE model obtained in this study range from 0.3 to 0.8 km, lower than the value of 2 km previously suggested for RSs in downward flashes. The obtained results support the assumption that the mode of charge transfer to the ground giving rise to MM pulses is similar to that of RSs. The results are also in support of the generally assumed similarity between M‐ICC pulses and classical MCs.